On the exit from a finite interval for the risk processes with stochastic premiums - Gusak, D.V.; Karnaukh, E.V. (Інститут математики НАН України, 2005)
We consider the almost semicontinuous step-process ξ(t). The conditional characteristic
functions of the jumps of ξ(t) have the form E [eiαξk /ξk > 0] = c(c − iα)−1.
For such processes, the boundary functionals related to the exit from a ﬁnite interval
are investigated.